(untitled) (Iter, 2022)
In this article. beauty> and discourse are studied from the viewpoint of rhetoric in both Plato and Aristotle. While in the former these aspects are considered in the perspective of a philosophical rhetoric. strongly committed to the knowledge of goodness and truth. in the latter emphasis is given on the rhetoric as an art. independently of epistemic and moral criterio. Despite of this difference. there are some common components too. especially in respect of their idea of beauty. which allon s us to realice a certain continuity beween the master and the disciple.